Concussion in motor sport: A medical literature review and engineering perspective. (October 2017) - Deakin, Naomi D; Cronin, Thomas; Trafford, Paul; Olvey, Stephen; Roberts, Ian; Mellor, Andrew; Hutchinson, Peter J
'WARNING: motor sport can be dangerous'. The spectrum of head injuries in motor sport has shifted dramatically in recent decades, fuelled by advances in medicine and engineering. Despite these successes, there are growing public and professional concerns regarding concussion in motor sport. This review appraises the published literature concerning concussion in motor sport, with particular focus on the current medical and technical challenges in the field. The incidence and assessment of concussion in motor sport is discussed, in addition to modifiable risk factors within and outside the automobile environment. Lastly, areas for further research and development are outlined.